1983
DOI: 10.1097/00000658-198303000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Local Recurrence of Breast Cancer as the First Site of Therapeutic Failure

Abstract: Sixty patients who had ipsilateral chest wall recurrence of breast cancer and no detectable distant metastases were evaluated retrospectively to determine the implications of chest wall recurrence as the first site of therapeutic failure. Mean time intervals between treatment of the primary breast cancer and discovery of local recurrence, between treatment of local recurrence and distant metastases, and between treatment of local recurrence and death in order and, respectively, in years for pathologic Stages I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 12 publications
2
38
1
2
Order By: Relevance
“…Even though we report all loco-regional recurrences during the observation time, which the CRC and NSABP studies do not, our figures are low (10, 1 I). from those of others in several reunlike Gilliland et al (12), whose findings suggested the loco-regional recurrence rate to be solely dependent on the initial stage of disease (l2), we found it to be related also to treatment: the recurrence rate in our postoperative radiotherapy subgroup was 7%), as compared with 17% in the subgroup without postoperative radiotherapy. This is also in accordance with earlier findings from the Manchester (I), CRC ( lo), and NSABP ( 1 1 ) trials although their loco-regional recurrence rates were much higher.…”
Section: Discussionsupporting
confidence: 76%
“…Even though we report all loco-regional recurrences during the observation time, which the CRC and NSABP studies do not, our figures are low (10, 1 I). from those of others in several reunlike Gilliland et al (12), whose findings suggested the loco-regional recurrence rate to be solely dependent on the initial stage of disease (l2), we found it to be related also to treatment: the recurrence rate in our postoperative radiotherapy subgroup was 7%), as compared with 17% in the subgroup without postoperative radiotherapy. This is also in accordance with earlier findings from the Manchester (I), CRC ( lo), and NSABP ( 1 1 ) trials although their loco-regional recurrence rates were much higher.…”
Section: Discussionsupporting
confidence: 76%
“…In a study by Gilliland et al all patients with LR developed distant metastases between 1.2 and 4.2 years and all died of disease between 2.5 and 7.2 years [14]. Other reports with longer term follow-up of up to 10 years among patients with LR after mastectomy have reported overall survival rates of 18-42% [14,17] and 10-year disease-free survival of 7-17% after the diagnosis of LR [15,16]. In contrast, the MD Anderson experience of 23 patients with LR after SSM and IBR revealed 61% of patients alive with no evidence of disease at a median follow-up of 26 months [3].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the MD Anderson experience of 23 patients with LR after SSM and IBR revealed 61% of patients alive with no evidence of disease at a median follow-up of 26 months [3]. However, survival after breast cancer has been consistently shown to be associated with stage and grade of the primary tumor [6,14,17,18], and therefore, distant relapse seen synchronously with LR can mostly be attributed to tumor biology rather than type of surgical treatment performed. However, not all local recurrences are equal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations